Cost analysis of using hybrid microwave post-sintered silicon nitride inserts - Ariff, Tasnim Firdaus; Iqbal, Mohammad; Bahar, Rubina (Trans Tech Publications, Switzerland, 2015)
Heat treatment is a process often used to improve product performance by increasing the strength of material or other desirable characteristics. Silicon nitride (Si3N4) tool insert is known for its attractive properties including high fracture toughness, strength and wear resistance at elevated temperatures. Heat treating these inserts by post-sintering them for 15 minutes at 600°C using conventional heating and hybrid microwave energy has prolonged tool life by 11-21% and 48-94% respectively. Machining was performed on a T6061 Aluminium alloy rod for tool life analysis at three different cutting speeds; 215, 314 and 393 m/min. Cost analysis is performed on these post-sintered Si3N4 inserts and found that there are economical benefits in the tooling cost when compared with the untreated Si3N4 inserts.